MAKING MATHEMATICS LEARNING MEDIA "BAKU UNIT BOARD" IN CLASS II MI SALAFIYAH SANTREN BANGILAN TUBAN - Anisah, Zulfatun; Irawan, Agus Wahyu; Syihabudin, A. (Journal of Community Engagement in Economics, 2023)
This community service is in the form of making media at MI Salafiyah Banjarworo Bangilan Tuban. The main purpose of this PkM is to produce a learning media product that can provide varied experiences so that it can stimulate student interest in learning and motivate students at MI Salafiyah Banjaworo Bangilan Tuban.With this PkM, it can help the performance of educators in the teaching and learning process and student are more enthusiastic in learning in class. The strategy used in this PkM activity uses a qualitative and contextual approach. By observing the teaching and learning process and the interaction of teachers and students at MI Salafiyah Banjaworo Bangilan Tuban.In making this learning media, researchers produced visual learning media in the form of standart unit boards. Which can be used in thematic subjects off third grade. Learning media has a an important role to increase the learning interest of elementary scholl students, especially the lower clas because they are not able to think abstractly so that the material taught by the teacher needs to be visualized in a tangible form.